Case report: Dupilumab leads to an increased chance of head and neck Staphylococcus aureus infection in atopic dermatitis patients - Chen, Min; Gao, Kai; Ali, Kamran; Shan, Jinpeng; Qiu, YunMi; Xie, Tianci; Yu, Yiling; Wu, Liming (Frontiers in Medicine, 2023)
Dupilumab was the first biological medication licensed to treat atopic dermatitis (AD), and it has shown remarkable effectiveness and safety in the treatment of moderate-to-severe atopic dermatitis. There are limited drug-related adverse events associated with dupilumab in atopic dermatitis (AD) treatment. Here, we present two cases of local Staphylococcus aureus infection during the treatment of atopic dermatitis with dupilumab.